Corporate Governance dan Dampaknya terhadap Kinerja Keuangan dan Nilai Perusahaan - Azhar Latief (Universitas Muhammadiyah Sumatera Utara, 2019)
The purpose of this research is to test and analyze the effect of profitability as measured by ROA, size as measured by total assets, and growth as measured by asset growth on firm value as measured by Tobin's Q; to test and analyze how corporate governance as measured by the CGPI scores moderates the effect of profitability, size, and growth on firm value.Data used in this research is secondary data. There are 126 population used in this research which is companies wereincluded in the CGPI rating in period 2012-2015 (pooled data). There are 32 samples(8 companies × 4 years of observation) was selected by using purposive sampling method. Analysis of the data used is multiple linear regression to identify the influence of dependent variable on independent variable and Moderated Regression Analysis (MRA) to identify how corporate governance moderatesthe effect of profitability, size, and growth on firm value.The result of this research showed that profitability has positive and significant effect on firm value, size has positive and insignificant effect on firm value, growth has negative and insignificant effect on firm value, corporate governance has reduced the effect of profitability on firm value, corporate governance hasn’t moderated the effect of size on firm value, and corporate governance hasn’t moderated the effect of growth on firm value.